Robust nonlinear control of a variable-pitch quadrotor with the flip maneuver. (June 2019) - Bhargavapuri, Mahathi; Sahoo, Soumya Ranjan; Kothari, Mangal; Abhishek,
Abstract: This paper presents robust nonlinear control of a variable-pitch quadrotor with the flip maneuver. Backstepping approach is chosen for nonlinear control design. A control allocation loop dynamically computes the blade pitch angle of each rotor. A systematic method to select controller gains is presented that ensures closed-loop stability. Detailed analysis of the flip maneuver in the presence of input saturation is presented for the first time. Performance of the proposed control law is first verified through simulation. This is then implemented on a PixHawk open source autopilot board and flight tests are performed on an off-the-shelf variable-pitch quadrotor frame.